Kajian Penambahan Pasta Umbi Bit Merah (Beta vulgaris L) dan Tepung Kacang Hijau (Phaseolus radiatus L) dalam Pembuatan Roll Cookies - Fadlan Hidayat; Anum Farida; Dewi Ermaya; Sholihati Sholihati (Department of Agricultural Engineering, Syiah Kuala University, 2019)
Abstrak. Umbi bit merupakan salah satu tanaman umbi-umbian yang banyak tumbuh di Indonesia dan tinggi akan kandungan antioksidan dan kandungan karbohidrat. Kandungan yang dimiliki umbi bit dapat dimanfaatkan untuk pembuatan roll cookies. Untuk meningkatkan nilai gizi rolled cookies, dapat menambahkan tepung kacang hijau. Penelitian ini bertujuan untuk mengkaji penambahan pasta umbi bit merah dan tepung kacang hijau terhadap tingkat kesukaan dan penerimaan rolled cookies yang dihasilkan. Rancangan penelitian yang digunakan adalah Rancangan Acak Lengkap (RAL) dengan 2 faktor yang diteliti. Faktor pertama adalah rasio tepung terigu dan pasta umbi bit merah yang terdiri dari 3 taraf yaitu R1=30:70, R2=50:50, R3=70:30. Faktor kedua adalah Persentase tepung kacang hijau yang terdiri dari 3 taraf yaitu K1= 50%, K2=40%, K3=30%. Setiap perlakuan diulang sebanyak 2 kali sehingga diperoleh 18 satuan percobaan. Pengamatan yang dilakukan terdiri dari uji hedonik dan tingkat penerimaan. Dari hasil penelitian dapat dinyatakan perlakuan berpengaruh sangat nyata (P≥0,01) terhadap uji hedonik yang meliputi (warna, aroma, rasa dan tekstur), dan sangat berpengaruh nyata (P≥0,01) terhadap tingkat penerimaan yang meliputi (warna, aroma, rasa, mutu hedonik rasa, tekstur, mutu hedonik tekstur dan keseluruhan). Formulasi terbaik rolled cookies berdasarkan parameter organoleptik diperoleh pada kombinasi K2R2. Rolled cookies terbaik memiliki tingkat kesukaan terhadap warna 3,71 (suka), aroma 4,48 (suka), rasa 4,43 (suka) dan tekstur 4,56 (suka), sedangkan tingkat penerimaan rolled cookies terhadap warna 4,53 (suka), aroma 4,53 (suka), rasa 4,56 (suka), mutu hedonik rasa 4,50 (suka), tekstur 4,50 (suka), mutu hedonik tekstur 4,56 (suka) dan penerimaan keseluruhan 4,23 (suka). Study of Addition of Red Bit Bulb Paste (Beta vulgaris L) and Green Bean Flour (Phaseolus radiatus L) in Making Roll Cookies Abstract. Beetroot is one of the tubers that grows in Indonesia and is high in antioxidants and carbohydrate content. Beetroot bulbs contain betalain pigments which are a combination of betasianin purple pigments and betasianin yellow pigments which function as natural dyes. Usually beetroot is consumed by juicing or processed again into fine texture food, but it is necessary to diversify beetroot products into attractive and popular products for consumption by the majority of Indonesians, for example rolled cookies. To increase the nutritional value of rolled cookies, other ingredients can be added such as green bean flour. This study aims to study the process of making rolled cookies from beets and also to determine the effect of adding green bean flour and the comparison of the number of beet paste and mung bean flour to the level of preference and acceptance of the resulting rolled cookies. The research design used was a Completely Randomized Design (CRD) with 2 factors studied. The first factor is the ratio of wheat flour and red beetroot paste consisting of 3 levels, namely R1 = 30: 70, R2 = 50: 50, R3 = 70: 30. The second factor is the percentage of green bean flour which consists of 3 levels, namely K1 = 50%, K2 = 40%, K3 = 30%. Each treatment was repeated 2 times to obtain 18 trial units. Observations made consisted of hedonic tests and acceptance levels. From the results of the study it can be stated that the treatment has a very significant effect (P10.01) on the hedonic test which includes (color, aroma, taste and texture), and is very significant (P≥0.01) on the level of acceptance which includes (color, aroma, taste, hedonic quality taste, texture, hedonic texture and overall quality). The best formulation of rolled cookies based on organoleptic parameters is obtained in the K2R2 combination. The best rolled cookies have a preference for color of 3.71 (likes), aroma of 4.48 (likes), flavor of 4.43 (likes) and flavor of 4.56 (likes), while the level of acceptance of rolled cookies is 4.53 ( likes), aroma 4.53 (likes), taste 4.56 (likes), hedonic quality taste 4.50 (likes), texture 4.50 (likes), hedonic quality texture 4.56 (likes) and overall acceptance 4 , 23 (likes).